Studi Kasus Pemenuhan Kebutuhan Personal Hygiene pada Pasien Post Natal Care (PNC) Bedah Sesar - Lena Atoy; Akhmad Akhmad; Riski Febriana (Poltekkes Kemenkes Kendari, 2019)
Sectio Caesarea is an artificial delivery in which the fetus is born through an incision in the abdominal wall and uterine wall with the uterine nerves intact and weighing more than 500 grams. Personal hygiene or personal hygiene is a person's effort to maintain the cleanliness of himself as a whole body for physical and psychological well-being. The medical record data of Dewi Sartika Kendari General Hospital, the number of mothers who gave birth in 2016 gave birth to a sectio caesarea as many as 496 people, then in 2017 there were 586 sectio caesarean deliveries, and in 2018 the number of sectio caesarean deliveries was 669 people. Purpose: to determine the care of post natal care patients with sectio caesarea in fulfilling personal hygiene needs. Results: The data were obtained from direct assessment, interviews, and looking at the patient's medical records, where at the time of the assessment, there were several complaints that the client complained about in fulfilling the client's personal hygiene needs so that a diagnosis was carried out where the diagnosis that was appointed in this case was a deficit of care. self: shower. The intervention was carried out in accordance with the existing theory, namely using the Nursing Outcomes Classification and Nursing Intervention Classification, the implementation was carried out for 3 days so that the results were that the client could carry out personal hygiene care independently with a little help from nurses and family.